1999
DOI: 10.1037/1064-1297.7.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated methylphenidate treatment in the young rat: Sensitization of both locomotor activity and stereotyped sniffing.

Abstract: The behavioral effects of repeated methylphenidate (MPH) treatment were assessed in young rats. In 4 experiments, rats (starting at Postnatal Day 10 or 16) were pretreated on 5 consecutive days with saline or MPH (2.5-20.0 mg/kg i.p.). Sensitization was assessed after 1 or 7 abstinence days, with rats receiving a test day challenge injection of either a low dose of MPH (2.5 mg/kg) or the same dose of MPH as given during pretreatment. Results show that a test day injection of 2.5 mg/kg MPH produced a sensitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 58 publications
4
58
2
3
Order By: Relevance
“…A dose of 10 mg/kg MP produces more locomotor activity than higher or lower doses of the drug (Gaytan et al 1997;Crawford et al 1998;McDougall et al 1999), an effect observed in both young and older animals. We found that 2 weeks following repeated treatment with MP (10 mg/kg IP), a threshold challenge dose of cocaine (7.5 mg/kg IP) significantly enhanced ambulations and rearing, as compared to saline-treated animals.…”
Section: Cross Sensitization From Mp To Cocainementioning
confidence: 93%
See 2 more Smart Citations
“…A dose of 10 mg/kg MP produces more locomotor activity than higher or lower doses of the drug (Gaytan et al 1997;Crawford et al 1998;McDougall et al 1999), an effect observed in both young and older animals. We found that 2 weeks following repeated treatment with MP (10 mg/kg IP), a threshold challenge dose of cocaine (7.5 mg/kg IP) significantly enhanced ambulations and rearing, as compared to saline-treated animals.…”
Section: Cross Sensitization From Mp To Cocainementioning
confidence: 93%
“…Unfortunately, animal studies have provided conflicting answers (Laviola et al 1995;Ujike et al 1995;Snyder et al 1998;Wood et al 1998;Izenwasser et al 1999;McDougall et al 1999;Zavala et al 2000). Sensitization to MP in rodent models has been well documented (Shuster et al 1982;Gaytan et al 1997;Crawford et al 1998; but see McNamara et al 1993), but the use of relatively high doses in most studies, and the apparent inability of MP to induce long-term locomotor sensitization in young animals (McDougall et al 1999), has raised questions regarding the clinical relevance of such findings (National Institute of Mental Health 1999).Animal studies have also shown that repeated exposure to psychostimulants increases the likelihood that rats will acquire drug self-administration (SA) with shorter latencies (Horger et al 1992) and at lower doses (Horger et al 1990), perhaps a more relevant display of sensitization as it relates to addiction. Pretreatment with such stimulants as nicotine, caffeine, and amphetamine produces enduring enhancements in the acquisition of cocaine SA (Valdez and Schenk 1994;Schenk and Davidson 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although relatively little is known regarding methylphenidate's propensity to induce neuronal alterations, a number of studies demonstrated that repeated methylphenidate treatment in animal models causes behavioral changes similar to other psychostimulants. These include increased psychomotor activation by a subsequent psychostimulant challenge (behavioral sensitization) (eg Shuster et al, 1982;Gaytan et al, 1997;Crawford et al, 1998;McDougall et al, 1999;Brandon et al, 2001), place preference conditioning (Martin-Iverson et al, 1985;Meririnne et al, 2001;Andersen et al, 2002), enhanced cocaine self-administration (Brandon et al, 2001;Schenk and Izenwasser, 2002), as well as several other behavioral changes (Bolanos et al, 2003;Carlezon et al, 2003). These behavioral effects indicate that methylphenidate can produce enduring neuronal changes.…”
Section: Introductionmentioning
confidence: 99%
“…Duke, O'Neal, and McDougall (1997) observed significant behavioral sensitization in rats given 2.5 mg/kg AMPH, twice daily, during PDs 17–20. Other studies applied only one daily dose of AMPH (1.0, 2.5 or 5.0 mg/kg) or MPH (5.0, 10.0 or 15.0 or 20.0 mg/kg) during PDs 17–20 (McDougall, Duke, Bolanos, & Crawford, 1994) or PDs 16–21 (McDougall, Collins, Karper, Watson, & Crawford, 1999) and reported behavioral sensitization when tested 24 or 48 hr after the induction phase.…”
Section: Discussionmentioning
confidence: 99%